Gestión administrativa del Cyber “Meganet Odalys” de la parroquia El Salto, cantón Babahoyo en el periodo 2022. - Aranda Vargas, Mercedes Cecilia (2023)
This case study has the objective of this study is to analyze the administrative processes that are developed in the cyber "Meganet Odalys" of the El Salto parish, which is based on the line of research Financial Management, administrative, tax, audit and control and the subline Companies and public and private institutions, in addition, it is carried out with the help of the respective methodology that refers to the use of descriptive, analytical and bibliographic methods that collect information based on the criteria of several authors with respect to the terms that arise from the topic raised; while the techniques that admit to obtaining the information are the interview carried out with the owner of the microenterprise and the questionnaire structure of ten questions that agree to know the criteria of internal clients. As a consequence, they allowed to identify that the company presents problems that are related to a deficient administrative management such as: the lack of planning of daily activities, it lacks an organizational structure (organizational chart), it does not have an established organizational culture, it lacks evaluation of the administrative processes carried out by the company, the administrator lacks technical skills to carry out the tasks for the development of specific activities, knowledge updates regarding administrative management are not carried out, he does not consider the necessary elements to generate strategies corporate, lacks a digital tool to control assets, limited staff for the development of activities and mismanagement of finances.